DIGITAL TECHNOLOGY IMPLEMENTATION AND ORGANIZATIONAL PERFORMANCE OF HIGHER EDUCATIONAL INSTITUTIONS IN MARINDUQUE - Ribleza, Adelene (International Journal of Arts, Sciences and Education, 2023)
The educational institution is one of the areas that integrate the use of digital technology in providing quality services to its stakeholders. Likewise, in the mission of the institution understudy on the pursuit of venturing into new frontiers of educational evolution and of entering in the era of the Industrial Revolution, it is timely to assess its digital management of the educational institutions. The evaluation of the extent and impact of this innovation in the educational system drives the researcher to undertake a study on Digital Technology Implementation and Organizational Performance of Higher Educational Institutions (HEIs) in Marinduque. The regular faculty members including the Dean and Department Heads of the institution were the respondents of the study. The study utilized the descriptive and qualitative type of research in assessing the implementation digital technologies and organizational performance of Higher Educational Institution in Marinduque. It was found out that there is a significant difference in the implementation of digital technologies among HEIs in terms of infrastructure, information system, and people. It is revealed also that there is a significant relationship between the performance of HEIs and digital technology implementation. Based on the findings, a framework for Digital Technology Implementation was proposed. Keywords: Digital technology, digital technology implementation, organizational performance, infrastructure, information system, people, instruction, research, extension, administration